Improved stochastic physics schemes for global weather and climate models. (18th September 2015) - Sanchez, Claudio; Williams, Keith D.; Collins, Matthew
Abstract : The importance of probabilistic weather predictions and climate projections is growing. One of the key elements of the former is stochastic physics, schemes that perturb some uncertain processes in a general circulation model (GCM), such as physical parametrizations or diffusion. They help to increase the ensemble dispersion of ensemble prediction systems (EPS) and in some cases improve certain atmospheric processes by noise‐induced drifts. We have developed a new configuration of stochastic physics schemes for the Met Office Unified Model (MetUM). It consists of an improved Stochastic Kinetic Energy Backscatter v2 (SKEB2), plus the Stochastic Perturbation of Tendencies (SPT). The improvements to SKEB2 remove spurious physical artefacts, e.g. a spurious wave caused by low‐wave‐number perturbations, and improve the resolution sensitivity of the scheme. The SPT produces a larger ensemble spread in the Tropics than present schemes, but its impact on long‐term climate budgets makes the use of conservation constraints for water vapour and energy essential. The new configuration produces a higher impact in the Tropics, increasing the ensemble spread and improving some long‐standing climate biases in areas of excessive convection, whilst minimizing the negative impact on tropical processes like tropical convective waves.